Characterisation of betatrophin concentrations in childhood and adolescent obesity and insulin resistance. Issue 1 (21st November 2014) - Wu, Shimin; Gao, Hongjie; Ma, Yumei; Fu, Lina; Zhang, Cai; Luo, Xiaoping
Abstract : Background and Objective: Betatrophin, a novel hormone, is correlated with insulin resistance and promotes pancreatic β‐cell growth in mice. The aim of this study was to determine circulating betatrophin levels in overweight or obese children and adolescents. Methods: The following pairs of subjects were included: (i) normal‐weight healthy (n = 27) and overweight or obese (n = 28); (ii) non‐insulin‐resistant overweight or obese (n = 25) and insulin‐resistant obese (n = 15); (iii) normal‐weight males (n = 18) and females (n = 20); (4) 5 to 8 yr olds (n = 20) and 8 to 14 yr olds (n = 18). Circulating betatrophin levels were measured using enzyme‐linked immunosorbent assay (ELISA). In addition, clinical data were recorded and anthropometrical measurements were performed. Results: Circulating betatrophin levels were increased significantly in obese children and adolescents with insulin resistance (365.77 ± 30.86 pg/mL) compared with overweight or obese subjects without insulin resistance (274.25 ± 26.52 pg/mL; p < 0.05). However, no differences in betatrophin levels were seen between lean and overweight or obese children (323.18 ± 25.91 vs. 348.27 ± 18.91 pg/mL, respectively; p > 0.05). In the normal‐weight cohort, males had higher serum betatrophin level than did females, and subjects <8 yr old had lower serum betatrophin levels compared with those >8 yr. Surprisingly, betatrophin concentrations were correlated negatively with body mass index (BMI), but not with the BMI Z‐score, in non‐insulin‐resistant children and adolescents. Conclusions: These results demonstrated that circulating betatrophin levels were increased in insulin‐resistant obese children or adolescents and might act as a potential biomarker of insulin resistance in these populations. Furthermore, serum betatrophin concentrations might vary during the development of children and adolescents, as well as between genders.